A Day I Ain't Never Seen Before : Remembering the Civil Rights Movement in Marks, Mississippi - Bateman, Joe B., 1942-; Arvedon, Richard; Greenberg, Cheryl Lynn (Book collections on Project MUSE., 2022)
"A Day I Ain't Never Seen Before is both an oral history of Marks, Mississippi and a memoir of Joe Bateman's--a white civil rights worker from Oklahoma--experiences there at the height of the Civil Rights Movement. We hear the voices of his neighbors, collaborators, and opponents as they describe their lives before and during the Movement, along with his own narration of the events. This book illuminates the thousands of ordinary people--Black and white, male and female, southern and northern, old and young--who provided the backbone, the spirit, and the power that brought about both the Civil Rights Act and the Brown decision and challenged the nation to do more. These people were the ground troops for Dr. King's dream and the embodiment of Malcolm X's warnings. And behind the more famous locales of the Movement--think Selma, Birmingham, Atlanta, and Greensboro--are hundreds of ordinary towns like Marks. It was in those places where the impacts of the Movement were most closely felt and where the day-to-day struggles were especially real. This book is about one such ordinary town full of regular people struggling to make their lives better. Yet while much of the story is local, it intersects the broader movement in many places both through specific events like the Poor People's Campaign, Freedom Summer, James Meredith's March against Fear, and Washington, D.C.'s Resurrection City, and through broader civil rights themes ranging from school desegregation to voting rights, from sit-ins to white violence. Indeed, A Day has been edited, annotated, and contextualized by Cheryl Greenberg, a scholar of African American history, with an eye towards connecting Marks to the larger Civil Rights Movement"--